(untitled) (Biological Sciences - PJSIR, 2008)
. Food and drug are taken for the survival and well-being of human race. Food-drug interaction occurs when food including beverages taken orally affects the properties of intestinal enzymes (P450), which alters pharmacokinetics, bioavailability and pharmacodynamics of the drug. The bioavailability of a drug determines its therapeutic value. An increase in the amount of a drug would produce undesired toxic effects; whereas a reduced amount would result in serious complications that could be termed as therapeutic failure. Such health hazards are more pronounced in elderly persons and those who are taking potent drugs to control/treat chronic diseases. Also, the severity of adverse effect depends on the therapeutic index of a drug, more pronounced for a drug with low therapeutic index. The food (nutrient)-drug interaction has been recognized as a major health issue in western countries. Popular health magazines, newspapers etc. often summarize researches published in scientific journals, proceedings of conferences in simple to understand language to educate and warn readers on the consequences of food (nutrient)- drug interaction etc. Several national health agencies are also involved in conducting surveys and devising policies to minimize food-drug interactions